Examining the sequelae of childhood trauma in forensic mental health - MacInnes, Marlene (The University of Edinburgh, 2014)
Introduction The aims of this thesis were twofold. The first was to systematically review the literature, on the influence of childhood trauma on psychopathology, across a range of forensic settings. The second was to complete an empirical study that examined the relationship between childhood trauma and insecure attachment patterns and psychopathology, risk, and engagement in therapy, in a forensic population. Method For the first aim database searches and hand searches of journals assessed against predefined criteria, identified 13 papers that were eligible for review.For the research study, 64 participants from three forensic secure hospitals completed three self-report questionnaires as part of a retrospective cross-sectional design. Data was also obtained from hospital records and clinical staff. Results The systematic review identified ten studies that were rated to be of good quality, two that were rated to be of fair quality and one that was rated as weak. Results identified a relationship between childhood trauma and psychopathology, but it is difficult to generalise findings due to the heterogeneity of this population. The research study found both childhood trauma and insecure attachment significantly predicted psychopathology and risk. No associations with engagement in therapy were found, but methodological reasons for this outcome were considered. Conclusion The systematic review highlighted that research in the area of childhood trauma and psychopathology in forensic settings is at an early stage, as most studies are small and cross-sectional. It discussed the need to develop further research to improve psychological treatment and reduce recidivism. Recommendations were made in the research study to routinely assess for childhood trauma and consider attachment patterns. Limitations in the design of the study were also acknowledged.
Keywords: child abuse; attachment; childhood trauma; engagement; forensic patient; mental disorder; prisoner; psychopathology; risk; criminal